2008
DOI: 10.1021/bi702480t
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Pyocyanin Biosynthetic Protein PhzS

Abstract: The human pathogen Pseudomonas aeruginosa produces pyocyanin, a blue-pigmented phenazine derivative, which is known to play a role in virulence. Pyocyanin is produced from chorismic acid via the phenazine pathway, nine proteins encoded by a gene cluster. Phenazine-1-carboxylic acid, the initial phenazine formed, is converted to pyocyanin in two steps that are catalyzed by the enzymes PhzM and PhzS. PhzM is an adenosylmethionine dependent methyltransferase, and PhzS is a flavin dependent hydroxylase. It has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
77
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 37 publications
2
77
0
Order By: Relevance
“…1E). We found that the deletion of mex leads to delayed wrinkling solely in strains capable of producing 5-Me-PCA (i.e., strains that contain the phenazine biosynthetic enzymes PhzA-G and PhzM) (43,44).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…1E). We found that the deletion of mex leads to delayed wrinkling solely in strains capable of producing 5-Me-PCA (i.e., strains that contain the phenazine biosynthetic enzymes PhzA-G and PhzM) (43,44).…”
Section: Resultsmentioning
confidence: 95%
“…5-Me-PCA, a reactive compound with a higher redox potential than the well-studied P. aeruginosa phenazines, has not been fully purified from wild-type P. aeruginosa cultures, although various observations indicate that it is the intermediate between phenazine-1-carboxylate (PCA) and pyocyanin in the phenazine biosynthetic pathway (38)(39)(40). Among these are the facts that the red phenazine aeruginosin A (5-methyl-7-amino-1-carboxyphenazinium betaine) is overproduced by P. aeruginosa phzS mutants (41,42), which lack the hydroxylase required to convert 5-Me-PCA to pyocyanin (43,44), and that E. coli expressing phzM converts PCA into a red pigment (42). Interestingly, the gene required for production of 5-Me-PCA from PCA, phzM, is located next to the mex operon on the P. aeruginosa chromosome (Fig.…”
mentioning
confidence: 99%
“…1A) (45). While both its precursor, PCA, and its derivative, pyocyanin, are detected at near millimolar concentrations in culture supernatants, the PhzM intermediate, proposed to be 5MPCA, has not been detected in supernatants and has been proposed to be unstable (4,13,39). In P. aeruginosa, phenazine production is controlled by a number of regulators, including those involved in cell density-dependent signaling, referred to as quorum sensing.…”
mentioning
confidence: 99%
“…The supernatant was then analyzed by an HPLC system equipped with a Shimadzu LCMS-2010EV single-stage quadruple mass analyzer. A parallel control reaction was carried out with 16 O 2 (air), and the product was analyzed. Liquid chromatography-mass spectrometry (LC-MS) analysis of time course of product formation.…”
Section: Methodsmentioning
confidence: 99%
“…Homology modeling. A BLASTP search with TMU-oxidizing enzyme and HpxO (30) as queries against the PDB identified a flavin-containing hydroxylase involved in pyocyanin biosynthesis (PhzS) from Pseudomonas aeruginosa (16) as the best match, with 30% sequence identity to both. PhzS belongs to the family of flavin-dependent aromatic hydroxylases, of which the best characterized is p-hydroxybenzonate hydroxylase (PHBH).…”
Section: Methodsmentioning
confidence: 99%